Social status, hukou conversion and upwards class mobility: evidence from Chinese rural‒urban migrants - Xiao Yu; Sixiang Cai; Xiaotong Yang; Yipu Cao; Wei Jiang (Humanities & Social Sciences Communications)
Abstract As a dual economy, China has experienced rapid urbanization in recent decades, as rural‒urban migrants have poured into cities in search of better work, competitive salaries, nonagricultural hukou, and upwards class mobility. The literature has fully discussed the impacts of migrants on China’s economy but has not focused enough attention on the psychological status of this particular group. This study takes China’s rural‒urban migrants as a representative research case and makes a clear distinction between policy-based and self-motivated migrants. By employing five waves of nationally representative Chinese General Social Survey (CGSS) data, we compare their subjective perceptions of social status, specifically, subjective social status (SSS) and subjective family economic status (SFES), to those of urban natives, which is one of the first studies to quantify this issue through econometric models. Contrary to earlier reports indicating that migrants always present self-perceived social inferiority, the empirical results show that both the current and future SSSs of self-motivated migrants are almost equal to those of urban natives, but the identity of being a self-motivated migrant has markedly negative effects on their SFES. Moreover, both the individual SSS and the SFES of policy-based migrants are significantly lower than those of urban natives are, and salient disparities can still be observed in individual SSS between them after ten years. Moreover, we identified that female migrants are at a disadvantage in terms of SSS and SFES. Our findings provide theoretical contributions for clearly distinguishing the types of Chinese rural–urban migrants and make realistic contributions to a transitional economy when implementing policies aimed at transforming migrants’ psychological conditions during the urbanization process.